2020
DOI: 10.9734/irjpac/2020/v21i2330319
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity and Total Phenolic and Flavonoid Contents of Methanolic Extracts of Urtica dioica L. by Different Extraction Techniques

Abstract: In this study, the efficacy of different extraction techniques (maceration, ultrasound-assisted and Soxhlet extraction) on the content of biologically active components in extracts from fresh and dried nettle leaves, and their antioxidant activity were analyzed. Methanol was used as the solvent. Total phenolic content and antioxidant capacity were determined by Folin-Ciocalteu, DPPH and FRAP methods, respectively. High content of total phenolic compounds and high antioxidant activity were recorded in extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
(43 reference statements)
2
6
0
Order By: Relevance
“…Figure 2 shows that Soxhlet extraction produces extracts with higher TFC than the extracts obtained by maceration. These results are similar to other studies of the methanol extracts of Urtica dioica [15][16] , the ethanol extract of Vernonia amigdalina 17 and the methanol extract of Rhaponticoides iconiensis 18 . The time needed for Soxhlet extraction is much less than for maceration, which required a minimum of three days.…”
Section: Total Flavonoid Contentsupporting
confidence: 92%
“…Figure 2 shows that Soxhlet extraction produces extracts with higher TFC than the extracts obtained by maceration. These results are similar to other studies of the methanol extracts of Urtica dioica [15][16] , the ethanol extract of Vernonia amigdalina 17 and the methanol extract of Rhaponticoides iconiensis 18 . The time needed for Soxhlet extraction is much less than for maceration, which required a minimum of three days.…”
Section: Total Flavonoid Contentsupporting
confidence: 92%
“…These values are higher than in commercially available vegetables. A comparison with the literature data is possible for U. dioica; considering our results, many studies have found total phenolic contents to be similar [23,[54][55][56] or higher [31,34,36,57] in leaves. In these latter works, the extraction phase was maximized by treatment at a high temperature (50 • C) or by sonication.…”
Section: Total Phenolic Contentssupporting
confidence: 65%
“…In addition, their solubility is contingent on several chemical features including the position of –OH groups, their molecular size, and length of the hydrocarbon chains ( 40 ). Polar solvents are often considered suitable to extract most of the phenolic compounds from plant tissues ( 41 , 42 ). MeOH has been found to be more efficient in extracting high content of low molecular weight phenolics from different plant parts ( 43 ).…”
Section: Resultsmentioning
confidence: 99%